Lead adsorption behaviours on nanoscale zero valent irons (nZVI) coupled with rice husk MCM-41 - C. Kaewbuddee; P. Chanpiwat; P. Kidkhunthod; K. Wantala (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aims of this work were to investigate the characteristics of nanoscale zero valent irons (nZVI) coupled with mesoporous materials (RH-MCM-41) adsorbent and to study the removal mechanisms of Pb (II) from synthetical solutions using full pictorial design batch experiments. Synthetic nZVI coupled with RH MCM-41 as Pb (II) adsorbent were characterized by XRD, TEM, BET and XANES. The results of XANES analyses confirmed the ability of RH-MCM-41 to prevent oxidations of Fe0 to Fe2+ and Fe3+. XANES results also verified the oxidation states of Pb (II). The solution pH was the most significant positive effect in controlling Pb (II) adsorption. The equilibrium and kinetic adsorption isotherms well fitted with the Langmuir isotherm. The pseudo-second order kinetic adsorption indicated that the adsorption process is the rate limiting step for Pb (II) removal. Furthermore, Langmuir-Hinshelwood confirmed the obvious Pb (II) adsorption at the active site of adsorbents. The reduction rate constant (kr = 5,000 mg/L.min) was higher than the adsorption rate constant (Kad = 0.0002 L/mg). Regarding the research results, four pathways including: reduction process, adsorption on FeOOH, adsorption on RH-MCM-41 and complex reaction between Fe and Pb ions were suggested for Pb (II) removal by nZVI coupled with RH-MCM-41.